1998
DOI: 10.1523/jneurosci.18-10-03803.1998
|View full text |Cite
|
Sign up to set email alerts
|

Long-Distance Axonal Regeneration in the Transected Adult Rat Spinal Cord Is Promoted by Olfactory Ensheathing Glia Transplants

Abstract: The lack of axonal regeneration in the injured adult mammalian spinal cord leads to permanent functional impairment. To induce axonal regeneration in the transected adult rat spinal cord, we have used the axonal growth-promoting properties of adult olfactory bulb ensheathing glia (EG). Schwann cell (SC)-filled guidance channels were grafted to bridge both cord stumps, and suspensions of pure (98%) Hoechst-labeled EG were stereotaxically injected into the midline of both stumps, 1 mm from the edges of the chann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
398
4
10

Year Published

1998
1998
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 651 publications
(420 citation statements)
references
References 65 publications
8
398
4
10
Order By: Relevance
“…Owing to these unique roles, OEC transplantation has emerged as a promising experimental therapy for axonal injuries and demyelinating disease [5]. Experimental studies have shown that OECs transplanted near nerve injury sites can not only promote the re-growth of injured axons [6][7][8], but also form myelin sheaths around demyelinated axons, leading to the restoration of axonal functions [9][10][11][12][13][14][15]. Moreover, transplantation of autologous OECs into the injured spinal cord in human is feasible and is safe up to 1 year after implantation [16].…”
Section: Introductionmentioning
confidence: 99%
“…Owing to these unique roles, OEC transplantation has emerged as a promising experimental therapy for axonal injuries and demyelinating disease [5]. Experimental studies have shown that OECs transplanted near nerve injury sites can not only promote the re-growth of injured axons [6][7][8], but also form myelin sheaths around demyelinated axons, leading to the restoration of axonal functions [9][10][11][12][13][14][15]. Moreover, transplantation of autologous OECs into the injured spinal cord in human is feasible and is safe up to 1 year after implantation [16].…”
Section: Introductionmentioning
confidence: 99%
“…Myelin sheaths made by transplanted glial cells en hance action potential conduction (20,21,39) and we have been able to show that both normal and transplantmediated remyelination results in restoration of function lost as a consequence of demyelination (22). In addition, Schwann cell and olfactory ensheathing cell transplanta tion, in the form of "bridges," provides a means of stim ulating regeneration of CNS axons (19,32). Glial cell transplantation may therefore provide a therapeutic strat egy for remyelinating areas of chronic demyelination and stimulating axon regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Since olfactory ensheathing cells (OECs) have been reported to enhance axonal regeneration in rat spinal cord when transplanted into lesion sites (Li et al, 1997;Ramon-Cueto et al, 1998), OECs have become a prime candidate for cell-mediated repair following a variety of Central Nervous System (CNS) lesions (Richter and Roskams, 2008) not only in animal model but also in clinical situation (Li et al, 1998;Dobkin et al, 2006;Franssen et al, 2007;Bauchet et al, 2008). More and more literature reviews give us more and more hope that OEC transplantation to be one of the most promising therapeutic strategies (Barnett and Riddell, 2007;Sasaki et al, 2007;Bauchet et al, 2008;Bunge, 2008;Radtke et al, 2008;Richter and Roskams, 2008;Kawaja et al, 2009); OECs have been successfully transplanted in acute (Resnick et al, 2003;Polentes et al, 2004;Collazos-Castro et al, 2005;Lopez-Vales et al, 2006;Andrews and Stelzner, 2007;Sasaki et al, 2007) and chronic (Andrews and Stelzner, 2004;Lopez-Vales et al, 2007) models of rodent spinal cord injury.…”
mentioning
confidence: 99%